The Use of Mobile-Based Android Media In Digital Marketing Learning To Improve Learning Motivation - Muslichun, Achmad; Rejekiningsih, Triana; Ardianto , Deny Tri; Mustagfirin, Mustagfirin; Choube, Pravin R. (Journal of Nonformal Education, 2026)
Background - The development of digital marketing competencies is essential in technology-driven industries. However, learning outcomes and students’ motivation in digital marketing courses at Magistra Utama Surakarta remain suboptimal due to the limited use of interactive and engaging learning media. Conventional teacher-centered instruction has not sufficiently supported students’ active participation in the learning process.Research Urgency - The need for innovative learning media in digital marketing education has become increasingly urgent, particularly in vocational and practice-oriented contexts. Android-based mobile learning offers a promising alternative to improve student engagement, motivation, and instructional effectiveness. However, empirical evidence regarding its effectiveness in digital marketing instruction is still limited.Research Objectives - This study aims to analyze the effect of Android-based mobile learning media, namely EDUMAGI, on improving students’ motivation in learning digital marketing at Magistra Utama Surakarta.Research Method - This study employed a quasi-experimental design with a pretest-posttest control group. Participants were selected using cluster random sampling. The experimental group received instruction using the Android-based mobile learning media EDUMAGI, while the control group was taught through conventional methods. Data were analyzed using an independent samples t-test with SPSS 27.Research Findings - The statistical analysis revealed a significant difference between the experimental and control groups (t = 6.338; p = 0.002 < 0.025), indicating that the implementation of Android-based mobile learning media resulted in higher student motivation scores. These findings demonstrate that EDUMAGI contributes to a more engaging, interactive, and effective learning experience in digital marketing instruction.Research Conclusion - Android-based mobile learning media significantly enhance students’ motivation in learning digital marketing. The use of EDUMAGI supports the integration of mobile learning as an effective alternative to conventional teacher-centered instructional approaches.Research Novelty/Contribution - This study provides empirical evidence of the effectiveness of EDUMAGI as a context-specific Android-based learning medium developed for digital marketing instruction. The findings contribute theoretically to the growing discourse on mobile learning adoption and practically offer an applicable instructional innovation for improving learner motivation and teaching quality in vocational education contexts.